Axle component separated ion-pair recognition by a neutral heteroditopic [2]rotaxane. - Knighton, R; Beer, P (2014)
A neutral heteroditopic pyridine N-oxide axle containing [2]rotaxane, synthesised via sodium cation templation, displays cooperative recognition of alkali metal cation-halide anion ion-pairs in an unprecedented axle component separated ion-pair binding fashion.